Multiple perspectives on the self in SLA, Editors: Sarah Mercer and Marion Williams, Publisher: Multilingual Matters, 2014, ISBN: 978-1-78309-134-8, Pages: 188. - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2015)
Book review